Does Home or School Matter More? The Effect of Family and Institutional Socialization on Religiosity: The Case of Hungarian Youth - Gabriella Pusztai; Gergely Rosta (MDPI AG, 2023)
The proportion of people who receive a religious upbringing at home and attend religious educational institutions varies across time and space. It is debatable how effectively various forms of religious socialization contribute to shaping one's religious identity. In Hungary, the proportion of young people receiving a religious upbringing is declining, but the church-run school sector is growing, which is accompanied by an increase in the proportion of pupils in a church-run school who do not receive a religious upbringing at home. This provides an opportunity to compare the impact of different socialization settings on religiosity. In the present study, we investigate how religious upbringing at home, church school attendance, and participation in religious education affect the different dimensions of young people's religiosity, hypothesizing that religious education within the family is decisive; but without it, the effect of the church school cannot be observed. For the analysis, we used data from the questionnaire-based Hungarian Youth Survey 2016 and 2020. Our results show that the influence of religious upbringing at home is dominant, but church schools significantly support young people's religious identity and practice without having an impact on the content of young people's beliefs and value preferences.